Identifikasi Pencemaran Merkuri di Tanah Lokasi Aktivitas dan Pasca Aktivitas Penambangan Emas Tanpa Izin di Desa Roko Kabupaten Halmahera Utara - Margaretha Tabita Tuny; Kurnia Kurnia; Tania Ayu Sudrajat; Kres Mahudin; Melisa Ganna; Defrit Luma (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Research has been carried out with the title identification of mercury pollution in soil at activity locations and post-unlicensed gold mining (PETI) activities in Roko Village, North Halmahera Regency, with the aim of determining the level of pollution and distribution of mercury at PETI and post-PETI activity locations. Sampling used the proportional sampling method in which 5 soil samples were taken at each location. Soil pH measurements were carried out in situ using a Soil Survey Instrument. To analyze mercury concentration in soil, soil samples were taken, preserved, prepared and tested for mercury concentration using a mercury analyzer. The analysis results show that the pH category at the PETI activity location is in the acid category with a pH range of 4.5-5. Meanwhile, the soil pH at the post-PETI location is in the acid to slightly acid category, namely pH 5-6. The results of the analysis of mercury concentrations in the soil at the PETI location ranged from 3.21 mg/kg - 74.99 mg/kg and post-PETI activity locations ranged from 1.76 mg/kg - 167.1 mg/kg at a radius of 0-50 m and has exceeded the normal criteria for mercury in soil and reached the very critical criteria category.